MANAJEMEN SARANA DAN PRASARANA UNTUK MENINGKATAN MUTU PEMBELAJARAN DI SMPN 3 SUBANG - Ramdani, Pajar; Asep Sutisna; Tatang Suryana; Maman Nuryaman; Rudi Kurniawan; Nurdiatul Jahroh; Faiz Karim Fatkhullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Infrastructure and facility management is a crucial factor in supporting the success of the learning process in schools. Effective and efficient management can create a conducive learning environment and improve the quality of learning. A common problem in schools is the suboptimal management of facilities and infrastructure, both in terms of planning, utilization, and maintenance, which impacts student learning processes and outcomes. This study aims to determine the management of facilities and infrastructure at SMP Negeri 3 Subang and its role in improving the quality of learning. This study used a qualitative approach with a mini-research method. Data collection techniques included observation, interviews with the principal and teachers, and documentation studies related to school facilities and infrastructure. The results indicate that the management of facilities and infrastructure at SMP Negeri 3 Subang has been implemented effectively through the planning, procurement, utilization, and maintenance stages and has made a positive contribution to improving the quality of learning. However, several obstacles remain, such as budget limitations and the lack of adequate maintenance of certain facilities. Therefore, it can be concluded that effective and sustainable management of facilities and infrastructure can improve the quality of learning at SMP Negeri 3 Subang.